The global impact of non-alcoholic fatty liver disease (including cirrhosis) in the elderly from 1990 to 2021 and future projections of disease burden - Siying Huang; Weitao Hu; Taiyong Fang (PLoS ONE, 2025)
Background Nonalcoholic fatty liver disease (NAFLD) is a metabolic disorder characterized by hepatic steatosis and inflammation in individuals with no significant alcohol consumption history. Predominantly affecting middle-aged and elderly populations, particularly those with obesity or metabolic syndrome, this condition represents a spectrum ranging from benign fatty accumulation to progressive liver damage. In advanced stages, NAFLD may progress to cirrhosis and hepatocellular carcinoma. This study systematically examines the global incidence patterns and epidemiological characteristics of NAFLD in older adults(>60 years), while establishing predictive models for its future disease burden. Methods Data on NAFLD in the Elderly(>60 years), from 1990 to 2021, was obtained from the Global Burden of Disease (GBD) study, encompassing 204 countries and territories. This dataset includes incidence rates of NAFLD. The Joinpoint regression model was utilized to detect turning points in the epidemiological trends of NAFLD, and decomposition analysis was performed to analyze the factors influencing these trends. To evaluate potential health disparities related to NAFLD, the Slope Index and Concentration Index were calculated. Additionally, the Norpred and Bayesian age-period-cohort (BAPC) models were employed to forecast future incidence rates of NAFLD. Results In 1990, the global NAFLD incidence in the elderly was 2819125(3972309 ± 1807520), with an ASIR of 568.46(803.33 ± 364.10). The global NAFLD prevalence in the elderly was 132549345(166820867 ± 102941502), with an ASPR of 27284.94(34321.92 ± 21200.69). The global NAFLD deaths in the elderly were 27864(45975 ± 15898), with an age-standardized death rate of 6.20(10.18 ± 3.55). The global NAFLD DALYs in the elderly were 559945(931920 ± 319045), with an age-standardized DALYs rate of 116.78(193.49 ± 66.73). In 2021, the global NAFLD incidence in the elderly was 7,012,128 (9,896,736 ± 4,480,162), with an ASIR of 636.90 (900.15 ± 406.76). The global NAFLD prevalence in the elderly was 366,363,498 (454,385,769 ± 287,891,088), with an ASPR of 33,576.22 (41,647.44 ± 26,372.13). The global NAFLD deaths in the elderly were 63,313 (99,891 ± 37,267), with an age-standardized death rate of 5.95 (9.39 ± 3.50). The global NAFLD DALYs in the elderly were 1,238,927 (1,973,042 ± 729,228), with an age-standardized DALYs rate of 113.95 (181.50 ± 66.91). From 1990 to 2021, the AAPC of ASIR for NAFLD in the elderly globally was 0.37(0.36 to 0.38), with a p-value < 0.05. The AAPC of ASPR for NAFLD in the elderly globally was 0.67(0.65 to 0.68), with a p-value < 0.05. The AAPC of age-standardized deaths rate for NAFLD in the elderly globally was −0.13(−0.16 to −0.1), with a p-value < 0.05. The AAPC of age-standardized DALYs rate for NAFLD in the elderly globally was −0.05(−0.07 to −0.02), with a p-value < 0.05. The decomposition analysis results indicate that population growth is the primary driver of increased disease burden in older NAFLD patients. It is expected that in the future, the disease burden of NAFLD in elderly people worldwide will continue to rise. Conclusions Over the past three decades, the annual age-standardized incidence rate and total number of cases of NAFLD, including cirrhosis, have increased among the elderly population, irrespective of gender. This upward trend is consistent across all SDI regions. Furthermore, future projections indicate that both the annual age-standardized incidence rate and the case numbers of NAFLD, including cirrhosis, in the elderly are likely to continue rising.